2002
DOI: 10.1002/yd.19
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent development in social and community context: A program of research

Abstract: Search Institute's integrated program of research on the linkages among community, developmental assets, and health outcomes is discussed. Recommendations are made for building a science that is dedicated to exploring pathways to developmental success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
11

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 49 publications
3
76
0
11
Order By: Relevance
“…Additionally, minority youth reported positive changes in their sense of mastery over stressful life situations. The capacity to resist negative peer pressures and to feel confident in managing difficult life situations are the types of personal coping resources and protective factors that have been found to promote healthy adolescent development (Benson, 2002;Eccles & Gootman, 2002;Larson, 2000;McLaughlin, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, minority youth reported positive changes in their sense of mastery over stressful life situations. The capacity to resist negative peer pressures and to feel confident in managing difficult life situations are the types of personal coping resources and protective factors that have been found to promote healthy adolescent development (Benson, 2002;Eccles & Gootman, 2002;Larson, 2000;McLaughlin, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The Search Institute (Benson, 2002;Benson, Mannes, Pittman, & Ferber, 2004;Benson, Scales, Hamilton, & Sesma, 2006;Scales, 1999), for example, has conceptualized the formation of a positive identity as a type of internal developmental asset focused on the development of personal power or sense of control, self-esteem, sense of purpose, and a positive view of the future (Scales, 1999). Lerner and colleagues (Lerner, 2005;Lerner et al, 2005) Both developmental assets and Five Cs models have thus conceptualized positive identity as a primarily internal attribute, one that is more closely aligned with values, skills, and competencies than with the relationships and opportunities available to youth.…”
Section: A Positive Identity Is a Developmental Assetmentioning
confidence: 99%
“…Moreover, Benson (2002) suggested that a community has the capacity to ensure that youth have external/ecological developmental assets but not necessarily that they have internal developmental assets such as a positive identity because internal assets evolve gradually as a result of numerous experiences. This view, however, appears to underrepresent the social facets of Erikson's (1963Erikson's ( , 1968 psychosocial formulation, and subsequent empirical findings have suggested a conceptualization that recalls Erikson's description of an individual's sense of identity as an inner sense of continuity and sameness matched by an outward sense of social continuity and sameness.…”
Section: A Positive Identity Is a Developmental Assetmentioning
confidence: 99%
“…PYD models focus on fostering the development of positive adjustment by pairing youth's innate capabilities with structured supports and opportunities. Supports and opportunities include family, neighborhoods, schools, congregations, youth organizations, and community-centered programs (Benson, 2002;Connell, Gambone, & Smith, 2000;Eccles & Gootman, 2002). It is generally recognized that the greater the number of opportunities available to youth, the greater the likelihood they will develop in pro-social ways (Benson, 2002;Eccles & Gootman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Supports and opportunities include family, neighborhoods, schools, congregations, youth organizations, and community-centered programs (Benson, 2002;Connell, Gambone, & Smith, 2000;Eccles & Gootman, 2002). It is generally recognized that the greater the number of opportunities available to youth, the greater the likelihood they will develop in pro-social ways (Benson, 2002;Eccles & Gootman, 2002). Successful youth development programs have been found to share several important characteristics.…”
Section: Introductionmentioning
confidence: 99%